Radiographers’ perceptions on the implementation of European BSS Directive (2013/59/Euratom): a local study - Anastácio, João (2022)
The field of medical imaging, like others in the area of healthcare provision, evolves and operates within complex environments. Thus, it must be a constant goal, maintaining and improving the levels of quality and safety, depending on the development of systems and a culture that can integrate individuals with technology and processes 1,2. The promotion of analysis or review of imaging procedures, motivated by the risk of ionizing radiation, is essential to improve the quality and related outcomes of care provided to the patient 3,4.